Determination of Total Selenium and Selenomethionine in cow milk by HPLC coupled to ICP-MS - Gueifão, Sandra (2012)
This study focused on the determination of total selenium and selenomethionine (SeMet) species in milk samples. Accurate determination of total selenium was carried out by Inductively Coupled Plasma Mass Spectrometry and Isotope Dilution (ID-ICP-MS). SeMet species was determined by a hyphenated technique, namely High Performance Liquid Chromatography coupled with ICP-MS equipped with a dynamic reaction cell (HPLC-DRC ICP-MS). In order to eliminate possible interferences (Ar-Ar, Ca-Ca and Ca-Ar) that occur either for determination of total selenium and SeMet, the DRC-ICP-MS operating conditions were optimized, using different flows of gases (Helium/Hydrogen) mixtures. The milk sample was digested by using a closed-vessel microwave system and various parameters, such as the ratio nitric acid/peroxide hydrogen, temperature, pressure and time were investigated. The ID was also compared with the standard addition method. Reproducibility, repeatability and trueness of the method for the determination of total selenium were evaluated using two reference materials, SRM-1549 and BCR-063R. The results obtained were in both cases in a good agreement with certified values. Both enzymatic and acid hydrolysis of the milk proteins were investigated as extraction procedures in view of SeMet determination in milk and the conditions used in this work seemed effective to achieve accurate determination of total selenium and SeMet in this difficult matrix.